A kérés beszédaktusának vizsgálata mozibüfés diskurzusok korpuszában - Pálfy-Madarász Eszter; Móra Kárpát-medencei Interdiszciplináris Szakkollégiumi Konferencia (3.) (2019) (Szeged) (2021)
In this research I attempted to examine the speech act of request in the corpus of cinema concessions discourse. My basic assumption is that there are countless strategies to perform a request to persuade the hearer to fulfil a request. An example of that is how to perform a request in a cinema concession, or in other catering facilities. The investigation is considered to be current in the field of linguistic pragmatics’ researches, because it focuses on the empirical aim of presenting and analysing the speech act of request in a specific, unique context (request in the cinema concessions). In the introductory section of this paper, I presented the most relevant literature on the topic, determined the theoretical background of the research (speech act theory, politeness theory, and conversation analysis). These three approaches enhanced the understanding of how requests could be analysed and understood in different terms of interaction. In this paper, I outlined only one research question: what kind of complex representation can be used in which we can not only examine the request as a speech act, but we can reflect on the whole context, the situational frame of the conversation and the situation of the participants? The purpose of the present study has been to investigate and describe a specific pragmatic phenomenon of the Hungarian language, it was a further goal to design and develop a comprehensive representation of a theoretical framework, in which requests could be observed and investigated as a speech act, reflecting on the actual context in which they are happening.
Keywords: Bölcsészettudományok; Nyelvek és irodalom